Perbuatan Kelalaian Oleh Konsultan Pengawas Konstruksi Atas Bangunan Yang Menyebabkan Kerugian Negara - Maulana, Irvan; Harisman, Harisman (Dinasti Research, 2024)
Construction supervision consultants are essential for infrastructure and construction projects that involve public funds. Construction supervision consultants are responsible for ensuring that projects run according to standards, comply with regulations, and reduce the risk of failure or accidents. Negligence committed by construction supervision consultants includes lack of supervision of project implementation to the point of not complying with established quality and safety standards. This study utilizes normative research methods, also known as legal research methods, positive legal research methods, doctrinal legal research methods, and pure legal research methods. During a construction project, the supervising consultant ensures that all work is carried out in accordance with the established technical specifications and quality standards. Ensuring that all projects are executed with professionalism and regulatory compliance, the consultant is responsible for reporting and documenting all important aspects of the project as well as managing changes that may occur during the construction process. The concept of negligence includes various types of non-compliance with technical standards, inaccurate planning, negligence in supervision and monitoring, corruption, and opacity in the construction process. The negligence of construction supervision consultants can negatively impact the success of the construction project itself.